The role of cGAS-STING signaling in rheumatoid arthritis: from pathogenesis to therapeutic targets - Zhu, Qiugang; Zhou, Huimin (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA) is a systemic autoimmune disease primarily characterized by erosive and symmetric polyarthritis. As a pivotal axis in the regulation of type I interferon (IFN-I) and innate immunity, the cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) signaling pathway has been implicated in the pathogenesis of RA. This pathway mainly functions by regulating cell survival, pyroptosis, migration, and invasion. Therefore, understanding the sources of cell-free DNA and the mechanisms underlying the activation and regulation of cGAS-STING signaling in RA offers a promising avenue for targeted therapies. Early detection and interventions targeting the cGAS-STING signaling are important for reducing the medical burden on individuals and healthcare systems Herein, we review the existing literature pertaining to the role of cGAS-STING signaling in RA, and discuss current applications and future directions for targeting the cGAS-STING signaling in RA treatments.